Factors influencing job performance: a case study amongst teaching staff in Kota Kinabalu Polytechnic - Harun, Amran; Sikul, Razinah; Mohtar, Tini Maizura; Datu Eranza, Datu Razali (2015)
The aim of this study is to identify the determinants of job performance among teaching staff in Kota Kinabalu Polytechnic. This study examined the relation of job satisfaction, demography factors (age and education), training and development, and compensation, with job performance. A total of 149 respondents were selected based on probability sampling. The potential respondents must have undergone at least 7 days of either internal or external training programme. Multiple regressions analysis was applied to verify the relationships of the study variables. The findings indicated that job satisfaction, age, training and development were important factors that affect job performance. Therefore, the study provides more understanding on the effect of job satisfaction on employee job performance, and proven the importance of training and development which can lead to a better job performance among employees.